KONFLIK INTERNAL DAN EKSTERNAL DALAM POLITIK KERAJAAN MATARAM ISLAM PADA MASA PEMERINTAHAN RAJA AMANGKURAT I (1646–1677) - Beriqtian Fernanda; Fahruddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The reign of Amangkurat I (1646–1677) in the Islamic Mataram Kingdom was marked by significant internal and external political conflicts that shaped the trajectory of the kingdom. Internally, the centralized and authoritarian policies of Amangkurat I sparked discontent among court nobles and regional leaders, leading to rebellions and power struggles within the kingdom. Externally, the kingdom faced pressures from expanding European colonial powers, particularly the Dutch East India Company (VOC), which exploited internal divisions to strengthen their influence. This study examines the dynamics of these conflicts, their causes, and their impacts on the stability and governance of the Mataram Kingdom. The findings highlight the interplay between internal factionalism and external intervention, which ultimately contributed to the weakening of Mataram’s sovereignty during this turbulent period.